Pomiar dokonań przedsiębiorstwa a rachunkowość zarządcza. Zarys genezy w teorii i praktyce - Nita, Bartłomiej (Corporate Performance Measurement and Management Accounting. Draft of the Origin on the Subject in Theory and Practice, 2008)
The paper deals with the origins of corporate performance measurement in the context of management accounting usage on the basis of the literature studies. In the first part of the article, the need for the performance measurement was discussed very briefly as well as the formation of management accounting was described in the chronological order. In the second part, the first uses of cost and management accounting with regards to performance measurement and evaluation in American enterprises were presented till the end of nineteenth century.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 87-95